1982
DOI: 10.1210/jcem-54-2-254
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Body Fat Distribution to Metabolic Complications of Obesity*

Abstract: The importance of body fat distribution as a predictor of metabolic aberrations was evaluated in 9 nonobese and 25 obese, apparently healthy women. Plasma glucose and insulin levels during oral glucose loading were significantly higher in women with predominantly upper body segment obesity than in women with lower body segment obesity. Of the former group, 10 of 16 subjects had diabetic glucose tolerance results, while none of the latter group was diabetic. Fasting plasma triglyceride levels were also signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
503
4
8

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,721 publications
(528 citation statements)
references
References 22 publications
13
503
4
8
Order By: Relevance
“…Obesity in the lower part of the body is less closely associated with the various metabolic complications of obesity as compared with the abdominal type (1,3,20). The metabolic differences between these depots provide a functional basis for these findings and also offer a likely explanation to the observation that the femoral-gluteal fat is difficult to reduce during caloric restriction in obese women (21).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in the lower part of the body is less closely associated with the various metabolic complications of obesity as compared with the abdominal type (1,3,20). The metabolic differences between these depots provide a functional basis for these findings and also offer a likely explanation to the observation that the femoral-gluteal fat is difficult to reduce during caloric restriction in obese women (21).…”
Section: Discussionmentioning
confidence: 99%
“…He noted that cardiovascular and metabolic complications of obesity were more common in patients with 'android' type of obesity (upper body obesity) when compared with 'gynoid' type (lower body obesity). Later on, several studies demonstrated the association of android (or central) obesity, hypertension, and insulin resistance, which formed the basis for understanding the pathophysiology of obesity-related hypertension (Kissebah et al 1982, Kalkhoff et al 1983, Modan et al 1985, for review see Landsberg et al (2013)). …”
Section: Introductionmentioning
confidence: 99%
“…There is a propensity to central obesity and visceral fat deposition is significantly increased compared to control subjects with similar BMI (6,7). In the general population, visceral adiposity is associated with the metabolic syndrome, insulin resistance/diabetes mellitus, hypercholesterolemia and hypertension (8,9).…”
Section: Introductionmentioning
confidence: 99%